Profil Pengobatan dan DRP’S pada Pasien Ganguan Lambung (Dyspepsia, Gastritis, Peptic Ulcer) Di RSUD Samarinda - Wahyu Widayat; Iffah Karina Ghassani; Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2018)
Gastric is the gastrointestinal organ which located after the esophagus before the duodenum and has a function in the process of food anabolism. Gastric disorders can be caused by Helicobacteria pylori infection, eating habit, stress, and side effects of NSAID drugs with the number of patients increasing each year. The purpose of this study is to analyze the characteristics and patterns of treatment in RSUD Samarinda to patients who have gastric disorders and DRP's profile. The research method used was non experimental. The data obtained were taken prospectively and the sampling technique used was incidental sampling. The research population were patients with gastric disorders (dyspepsia, gastritis, peptic ulcer disease) who were undergoing therapy at RSUD Samarinda. The results showed that patients with gastric disorders were dominated by women (55.7%), elderly 46-55 years old (36.5%), elementary school educational background (40.4%), private employees(36.5%), taking NSAID drugs (59.6%) and smoke (65.2%). Patients often eat spicy (82.7%), drink coffee (53.8%), and do not eat regularly (17.3%). Meanwhile, the patients receiving treatment pattern at the hospital were given treatment pattern 1 (36,5%), treatment pattern 4 (57,7%), treatment pattern 13 (58,8%). Presumptions towards DRPs profile is moderate drug interactions 80.6% and minor drug interactions 12.8%. As much of 23% of the patients showed certain indication but did not given any therapy, while as much of 5.7% of the patients were getting therapy without showing certain indication. As much of 65.4% patients take herbs (Turmeric and Curcuma) Keywords: DRP’s, Dyspepsia, Gastritis, Peptic Ulcer